Prototype Of A Web-Based Human Capital Information System Using SCRUM Method - Aziza, Yumaika Nistia; Abdillah, Leon A. (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2024)
The Human Capital Information System (HCIS) is software that manages staff data, payroll, and other everyday duties in the Human Capital sector. The Human Resources Management System aims to increase performance and eliminate mistakes in business processes to aid operational operations in the human resources department, particularly in recruiting, personnel data management, wage calculations, and promotions. While the system construction pipeline follows an SCRUM strategy for pipeline planning, which includes storyboarding (product owner) based on features to be generated, a product backlog, sprints, daily SCRUM, and sprint reviews, we also utilize qualitative data collecting approaches. This IS is connected with employee attendance, the human resource management system may help gather data and information on employee attendance in an accurate and efficient manner, as well as speed up and reduce mistakes in computing employee wages.